Effects of blood flow restriction on motoneurons synchronization - Taleshi, Mansour; Bubeck, Franziska; Gizzi, Leonardo; Vujaklija, Ivan (Frontiers in Neural Circuits, 2025)
Blood flow restriction (BFR) is a peripheral intervention that induces transient and reversible physiological perturbations. While this intervention offers a unique model to explore neuromuscular responses in multiple contexts, its impact on neural input to motoneurons remains unclear. Here, the influence of BFR on muscle force control, behavior, and neural input to motoneurons during isometric-trapezoidal and isometric-sinusoidal little finger abduction precision tasks has been studied. Sixteen healthy participants performed the tasks under pre-BFR, during BFR, and at two post-BFR conditions. High-density surface electromyography (EMG) was recorded from the abductor digiti minimi muscle, and motor unit spike trains (MUST) were decomposed using blind source separation technique. Coherence between cumulative spike trains (CSTs) of identified motor units was calculated to assess common synaptic input in the delta and alpha frequency bands. As expected, during BFR application, participants reported higher level of discomfort and significant deterioration in force-tracking performance, as measured using root mean square error (RMSE). Following the BFR release, the level of discomfort, along with impaired neuromuscular performance were reduced to pre-BFR condition. Coherence analysis revealed a prominent peak in the alpha band. The mean z-score coherence in the alpha band showed a reduction of 27% for isometric-trapezoidal and 31% for isometric-sinusoidal conditions from pre-BFR to BFR, followed by a rebound post-BFR intervention with increases of 13% and 20%, respectively. In the delta band, coherence values were consistently higher during sinusoidal tasks compared to trapezoidal ones. These findings indicate that brief BFR application led to decrease in motoneuron synchronization and force control precision likely due to desensitization as shown by changes in coherence alpha band.